Influence of differential longitudinal cyclic pitch on flight dynamics of coaxial compound helicopter - Ye Yuan (Chinese Journal of Aeronautics, 2023)
The Differential Longitudinal Cyclic Pitch (DLCP) in coaxial compound is found to be useful in mitigating low-speed rotor interactions and improving flight performance. The complex mutual interaction is simulated by a revised rotor aerodynamics model, where an improved Blade Element Momentum Theory (BEMT) is proposed. Comparisons with the rotor inflow distributions and aircraft trim results from literature validate the accuracy of the model. Then, the influence of the DLCP on the flight dynamics of the aircraft is analysed. The trim characteristics indicate that a negative DLCP can reduce collective and differential collective inputs in low speed forward flight, and the negative longitudinal gradient is alleviated. Moreover, a moderate DLCP can reduce the rotor and total power consumption by 4.68% and 2.9%, respectively. As DLCP further increases, the increased propeller power and unbalanced thrust allocation offset the improvement. In high-speed flight, DLCP does not improve the performance except for extra lateral and heading stick displacements. In addition, the tip clearance is degraded throughout the speed envelope due to the differential pitching moment and the higher thrust from the lower rotor. Meanwhile, the changed rotor efficiency and induced velocity alter low-speed dynamic stability and controllability. The pitch and roll subsidences are slightly degraded with the DLCP, while the heave subsidence, dutch roll and phugoid modes are improved. Lastly, the on-axis controllability, including collective, differential collective pitch, longitudinal and lateral cyclic pitches, varies with DLCP due to its effect on rotor efficiency and inflow distribution. In conclusion, a reasonable DLCP is recommended to adjust the rotor interaction and improve aircraft performance, and further to alter the flight dynamics and aerodynamics of aircraft.